Energy dissipation of rammed earth-timber joints under cyclic loading. Issue 145 (June 2021) - Luo, Yi; Zhou, Peisong; Ma, Huihuan; Ni, Pengpeng; Ding, Nan; Xu, Yuye
Abstract: Rammed earth-timber joints without enlarged ends have been used in rammed earth buildings for several hundreds of years. Due to the embedment nature, the joint has a certain degree of flexibility, allowing the floor and roof beams to slide without damaging the rammed earth, enabling dissipating energy during earthquakes. The energy dissipation mechanism of rammed earth-timber joint has not yet been fully understood. This study studied the energy dissipation characteristic of eight rammed earth-timber joint specimens via cyclic pull-out/push-in experiments, investigating the effects of compressive loading, embedment length, and surface roughness on joint performance. Results show that the joint stiffness under cyclic loading was reduced nonlinearly with the increase of pull-out displacement until the occurrence of slippage. The high vertical compression from the upper level, the deformability of timber frames, and the plasticity of rammed earth were found to be the primary energy dissipators. A linear frictional and nonlinear geotechnical hysteretic model, combining frictional and soil mechanics theories, was established to represent the joint behavior. In addition, a simplified multi-linear hysteretic model was developed for the same purpose. The predictions and the measurements had good agreement, suggesting that geotechnical methods should be employed to analyze the joint, maintaining the assumption that both the timber frame and the rammed earth are linear-elastic. Highlights: Energy dissipation of rammed earth-timber joint was investigated experimentally. Effects of compressive loading, embedment length, and surface roughness on joint performance were studied. Stiffness of rammed earth-timber joint under cyclic loading was reduced nonlinearly until slippage. Vertical compression, deformability of timber frames, and rammed earth plasticity were the primary energy dissipators. Two hysteretic models were established to represent the behavior of rammed earth-timber joint.